Saccharification of Agricultural Lignocellulose Feedstocks and Protein-Level Responses by a Termite Gut-Microbe Bioreactor - Rajarapu, Swapna Priya; Scharf, Michael E. (Frontiers in Energy Research, 2017)
This study investigated saccharification and protein-level responses to the candidate biofuel feedstocks corn stover (CS) and soybean residue (SR) by the gut of a lower termite. The focus termite in this work was Reticulitermes flavipes, which is a highly efficient lignocellulose digester that houses a mixture of prokaryotic and eukaryotic microbes in its gut. Our specific objectives were to (i) measure saccharification potential of the CS and SR feedstocks by termite gut protein extracts, (ii) identify specific proteins in the termite gut responding to feeding on CS and SR diets, and (iii) evaluate gut lignocellulase and accessory enzyme activity responses to CS and SR feeding. Cellulose paper was the control diet. Although CS was saccharified at higher levels, termite gut protein extracts saccharified both CS and SR irrespective of feedstock loading. Consumption of the CS and SR feedstocks by termites resulted in surprisingly few differences in gut protein profiles, with the main exception being elevated myosin abundance with SR feeding. Activity of potential lignocellulases and accessory enzymes was generally similar between CS and SR fed guts as well; however, cellobiohydrolase/exoglucanase activity was higher with CS feeding and glutathione peroxidase activity with SR feeding. These findings have significance from two perspectives. First, SR feeding / digestion appears to cause physiological stress in the termite gut that likely would extend to other types of microbial environments including those within industrial bioreactors. Second, because termites can survive on exclusive CS and SR diets and their guts exhibit clear CS and SR saccharification activity, this validates the R. flavipes system as a potential source for CS and SR degrading enzymes; in particular, cellobiohydrolases/exoglucanases and glutathione peroxidases from this system appear to play roles in CS and SR breakdown.